2002
DOI: 10.1016/s1470-0328(02)01910-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin A deficiency during pregnancy on maternal and child health

Abstract: Objective To examine the association between biochemical vitamin A deficiency in pregnancy and maternal and fetal health. Design A cross sectional clinical study.Setting Antenatal clinic of nutrition unit of Niloufer Hospital catering for a low socio-economic population, and a private nursing home (Swapna nursing home) catering for a high socio-economic population. Population 736 pregnant women in their third trimester of pregnancy belonging to low (n ¼ 522) and high socio-economic groups (n ¼ 214). Methods Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 9 publications
2
20
0
9
Order By: Relevance
“…In a systematic review, vitamin A supplementation during pregnancy was found to reduce anaemia risk (haemoglobin < 11.0 g/dL) among both anaemic and non-anaemic women (Thorne-Lyman and Fawzi, 2012). This is consistent with observational and intervention studies in women and children which showed correlations between anaemia and vitamin A deficiency and the amelioration of anaemia by improving vitamin A status in deficient populations (Radhika et al, 2002;Semba and Bloem, 2002;Al-Mekhlafi et al, 2013). In non-anaemic subjects, a test meal containing 1 000 µg retinol did not enhance iron absorption (Walczyk et al, 2003).…”
Section: 37supporting
confidence: 89%
“…In a systematic review, vitamin A supplementation during pregnancy was found to reduce anaemia risk (haemoglobin < 11.0 g/dL) among both anaemic and non-anaemic women (Thorne-Lyman and Fawzi, 2012). This is consistent with observational and intervention studies in women and children which showed correlations between anaemia and vitamin A deficiency and the amelioration of anaemia by improving vitamin A status in deficient populations (Radhika et al, 2002;Semba and Bloem, 2002;Al-Mekhlafi et al, 2013). In non-anaemic subjects, a test meal containing 1 000 µg retinol did not enhance iron absorption (Walczyk et al, 2003).…”
Section: 37supporting
confidence: 89%
“…La deficiencia de vitamina A (DVA) es un problema de salud pública en el mundo, que durante el embarazo se ha asociado con incremento en la morbilidad y mortalidad materna e infantil (16,17). Estudios en humanos y animales gestantes con concentraciones anormales de retinol sérico, han descrito la aparición de anormalidades obstétricas como malformaciones fetales, retardo del crecimiento intrauterino y abortos espontáneos durante la gestación (16,17).…”
Section: Introductionunclassified
“…Estudios en humanos y animales gestantes con concentraciones anormales de retinol sérico, han descrito la aparición de anormalidades obstétricas como malformaciones fetales, retardo del crecimiento intrauterino y abortos espontáneos durante la gestación (16,17). En estudios de mujeres gestantes con bajos niveles séricos de vitamina A se han reportado un mayor riesgo de infecciones puerperales y genitourinarias (18), pre-eclampsia (19), bajo peso neonatal o parto prematuro (20).…”
Section: Introductionunclassified
“…Algunos autores han señalado que una concentración sérica menor a 30 µg/dL podría definirse como deficiente durante el embarazo (21). Adicionalmente, se ha descrito que probablemente la baja ingesta de vitamina A contribuya a la aparición de la anemia durante el embarazo, de alta prevalencia en Sudamérica, ya que esta vitamina contribuye a la absorción y utilización del hierro, factor que no fue determinado en el presente estudio (22,23).…”
Section: Discussionunclassified